Adaptable DNA Storage Coding: An Efficient Framework for Homopolymer Constraint Transitions - Gao, Yunfei; No, Albert (IEEE access, 2024)
Many DNA storage codes take into account homopolymer and GC-content constraints. Still, these codes often need to meet additional practical database requirements, such as error correction and data queries, necessitating considerable financial and time investment in their training or design. As DNA storage technologies, including sequencing and synthesis, continue to evolve rapidly, these codes may need to be retrained or redesigned to adapt to new constraints. In this study, we aim to design a method for adapting an existing DNA storage code to satisfy a new constraint, specifically concerning homopolymer variations. We present a simple and effective framework known as Transfer Coding, which directly maps DNA sequences from an original homopolymer constraint [Formula Omitted] to a new constraint [Formula Omitted]. This approach essentially combines the existing coding scheme with a Transfer encoder. The proposed method uses strategic base replacements to ensure compliance with constraints, achieving results close to the theoretical limit while keeping alterations to the original sequence minimal.